The factors affecting the physical development of neonates in pregnant women with or without gestational diabetes mellitus. - Xiaodi Zhao; Nana Li; Runping Jia; Shumin Chen; Ling Wang (PLoS ONE)
Objectives To explore the factors affecting neonatal physical development in pregnant women with or without gestational diabetes mellitus (GDM). Methods The subjects were selected from the pregnant woman giving birth in 2nd Affiliated Hospital of Zhengzhou University, from November 2015 to May 2016. The age, occupation, education level, gestational age, body weight before pregnancy, body weight at delivery, body height, delivery pattern, GDM status of pregnant women and neonatal gender, birth weight (BW), chest circumference (CC), head circumference (HC) and birth length (BL) were collected through medical records and questionnaires. The clinical data were retrospectively analyzed and studied. Results The significant differences were found between women with GDM and without GDM in following neonatal variables (P<0.05): BW, CC, and HC. GDM status increased the incidence of macrosomia (OR = 2.241, 95% CI: 1.406-3.573), large CC (OR = 2.470, 95% CI: 1.687-3.6153). Gestational weight gain (GWG) above IOM guideline was risk factor for macrosomia (OR = 1.763, 95% CI:1.098-2.833), large HC (OR = 1,584, 95% CI: 1.093-2.296) and large CC (OR = 1.707, 95% CI:1.163-2.506). Underweight was risk factor for short BL (OR = 2.543, 95% CI:1.161-5.571) and small CC (OR = 1.901, 95% CI:1.064-3.394). Female neonate was prone to appear short BL(OR = 2.831, 95% CI: 1.478-5.422) and small HC (OR = 2.750, 95% CI: 1.413-5.350), and not likely to macrosomia (OR = 0.538, 95% CI: 0.343-0.843), longer BL (OR = 0.584, 95% CI: 0.401-0.850), large HC (OR = 0.501, 95% CI: 0.352-0.713), and (OR = 0.640, 95% CI: 0.446-0.917). For women with GDM, gestational age was an risk factor of neonatal BW (low BW: OR = 0.207, 95% CI: 0.085-0.503; macrosomia: OR = 1.637, 95% CI: 1.177-2.276), BL (short BL: OR = 0.376, 95% CI: 0.241-0.585; long BL: OR = 1.422, 95% CI: 1.054-1.919), HC (small HC: OR = 0.343, 95% CI: 0.202-0.583; large HC: OR = 1.399, 95% CI: 1.063-1.842) and CC (small CC: OR = 0.524, 95% CI: 0.374-0.733; large CC: OR = 1.485, 95% CI: 1.138-1.936). Conclusions In our study, gestational age, GDM status, neonatal gender, GWG and pre-pregnancy body mass index (BMI) are associated the abnormal physical development of neonates. In women with GDM, gestational age was correlate with neonatal abnormal physical developments.